Ebstein's anomaly associated with splenomegaly and reversible hypersplenism. Issue 4 (April 1991) - Bennett, M R; Shiu, M F
Abstract : A case of Ebstein's anomaly associated with chronic right heart failure, hepatosplenomegaly, and the haematological features of hypersplenism is presented. The haematological abnormalities were corrected after tricuspid valve replacement but recurred with the reemergence of clinical features of right heart failure.